(untitled) (International Journal of Architecture and Urbanism, 2025)
Urban buildings often disconnect occupants from nature, primarily due to the increasing scarcity of land. Many urban planners prioritize economic value, favoring built structures over green spaces, as buildings can accommodate various activities. This disconnection negatively impacts occupants’ psychological well-being, depriving them of spaces to relieve stress and fatigue, which can ultimately reduce productivity. To address this issue, the design of office and automotive centers on Basuki Rahmat Street, a high-density area in Surabaya, is proposed to promote an environmentally friendly approach while also addressing the challenges of typical urban development and enhancing the surrounding business district. By applying biophilic design principles, the building aims to foster a strong connection with nature. This strategy not only challenges conventional urban development patterns but also strengthens the district’s sustainability and livability. The automotive-related function of the site can be preserved and integrated with natural elements, creating a dynamic and interactive space. This fusion offers occupants a new way to engage with their surroundings while maintaining the site’s original character. Additionally, the building is designed with flexible spaces to accommodate the evolving needs of modern urban areas. Ultimately, this project seeks to redefine the relationship between architecture and nature in dense urban settings, offering a sustainable and human-centered solution to the challenges of urbanization.